FRET-based characterization of K264A, D345A, and Y335A mutants in the human dopamine transporter - (:unkn) unknown (My University, 2017)
0

The dopamine transporter (DAT) plays a role in the termination of dopaminergic neurotransmission; thereby it is accepted as the primary target of various psychostimulants. N-terminal phosphorylation of DAT has been proposed as a regulator in different DAT functions, such as amphetamine-induced efflux or PKC/PKA-mediated responses. To understand the role of N-terminal conformational changes in dopamine transporter structure and function, the fluorescence resonance energy transfer (FRET) method was applied to various DAT constructs fluorescently labeled at the N-terminus and substrate-induced conformational changes were determined using rhodamine-labeled cocaine analog JHC1-64 in three DAT mutants. The results indicated that the construct with YFP inserted into the N-terminal position-55 displayed effective interaction with the substrate and simultaneous mutation of two serine residues (S7 and S12) to alanine or aspartic acid demonstrated similar phenotypes as their wild-type (WT) counterparts. FRET was detectable for N-terminal p55 YFP WT, Ser/Ala, and Ser/Asp forms, but there was no significant difference among the three mutants, contrary to our expectations based on the previously proposed roles of these serine residues. In addition, three mutants (K264A, D345A, and Y335A) implemented in the position-55 YFP background were also investigated and the importance of Y335 in the translocation cycle and in the process of substrate release was verified.
Keywords: Biyoloji